Analysis of Barriers to Green Data Centers Implementation in Malaysia, using Interpretive Structural Modelling (ISM) - Harun, Hasbullah (Information Management and Business Review, 2023)
The data center market is expected to grow at 7% during 2022- 2027 and the market size is to reach RM2.0 billion in 2027. The high impact of ICT contributes to high energy consumption, which will impact the environment and greenhouse gas emissions. To reduce energy consumption is to introduce a green data centre. Implementing a green data center involves the introduction of energy-efficient measures for the data center. This will include using energy-efficient ICT equipment and energy-efficient facilities equipment, especially the HVAC system. The successful introduction of the green data center involves new technologies in which there will be barriers that need to be addressed. Based on the study, green awareness and the benefit of switching to green data centers is essential for green data center initiatives in Malaysia.